The emergence of the classical style in Greek sculpture - Neer, Richard T. (University of Chicago Press, 2010)
In the fifth century B.C.E, an artistic revolution occurred in Greece, as sculptors developed new ways of representing bodies, movement, and space. The resulting "Classical" style would prove influential for centuries and millennia to come. Modern scholars have traditionally described the emergence of this style as a steady march of progress, culminating in masterpieces like the Parthenon sculptures. But this account assumes the impossible: that the early Greeks were working tirelessly toward a style of which they had no prior knowledge. In this ambitious work, Richard Neer draws on recent ...